Effects of Plant Size, Temperature, and Light Intensity on Flowering of Phalaenopsis Hybrids in Mediterranean Greenhouses - Roberta Paradiso; Stefania De Pascale (The Scientific World Journal)
Mediterranean greenhouses for cultivation of Phalaenopsis orchids reproduce the warm, humid, and shaded environment of tropical underbrush. Heating represents the highest production cost, due to the high thermal requirements and the long unproductive phase of juvenility, in which plants attain the critical size for flowering. Our researches aimed to investigate the effect of plant size, temperature, and light intensity, during the phase of flower induction, on flowering of modern genotypes selected for Mediterranean greenhouses. Three experiments were carried out to compare (i) plant size: reduced size versus size considered optimal for flowering (hybrids “Sogo Yukidian,” “Chain Xen Diamond,” and “Pinlong”); (ii) temperature: moderate reduction of temperature versus standard thermal regime (hybrid “Premium”); (iii) light intensity: supplemental lighting versus reference light intensity (hybrid “Premium”). The premature exposure of plants to the inductive treatment delayed the beginning of flowering and reduced the flower stem quality, in all the tested hybrids. In “Premium,” the lower temperature did not affect flowering earliness and commercial quality of flower stems compared to the standard regime, whereas it promoted stem branching. In the same hybrid, supplemental lighting anticipated flowering and promoted the emission of the second stem and the stem branching, compared to the reference light regime.